The best of world SF. Volume 1 - Tidhar, Lavie (Head of Zeus, 2021)
"26 new short stories representing the state of the art in international science fiction, selected by Lavie Tidhar. The Best of World SF draws together stories from across the spectrum of science fiction - expect robots, spaceships and time travel, as well as some really weird stuff - representing twenty-one countries and five continents."--Provided by publisher.